Native T1 and T2 mapping by CMR in lupus myocarditis: Disease recognition and response to treatment. (1st November 2016) - Hinojar, Rocio; Foote, Lucy; Sangle, Shirish; Marber, Mike; Mayr, Manuel; Carr-White, Gerry; D'Cruz, David; Nagel, Eike; Puntmann, Valentina O.
Abstract: Background: Lupus myocarditis is likely more common than recognized clinically due to non-specific symptoms and lack of reliable non-invasive diagnostic tests. We investigated the role of native T1 and T2 in recognition of active myocardial inflammatory involvement in patients with systemic lupus erythematous (SLE). Methods: 76 patients with clinically suspected lupus myocarditis (14 males, age: 44 ± 16 years) underwent quantitative tissue characterization with native T1 and T2 mapping. Normotensive healthy subjects taking no medication served as controls (n = 46). Follow-up CMR studies were performed in a total of 35 subjects of which 14 patients received intensified anti-inflammatory treatment, as guided by SLE disease activity. Results: Compared to controls SLE patients had higher inflammatory markers, LV mass, native T1 and T2 values, and reduced longitudinal strain (p < 0.01). In patients with a positive troponin test (n = 36; 46%), native T1 and T2 were significantly higher (p < 0.01) with otherwise similar proportions of diffuse perimyocardial LGE (33%) and pericardial effusion (32%). Sixty-nine patients (83%) had an abnormal native T1, whereas 51 (71%) met diagnostic criteria for acute myocarditis. Follow-up CMRs revealed significantly greater reduction in native T1 and T2 values in patients with intensified anti-inflammatory treatment (p < 0.001) with the greatest change observed within the first follow-up period and plateauing thereafter. Native T1 and T2 were significant predictors of treatment response. Conclusions: Native T1 and T2 mapping support recognition of lupus myocarditis and reflect the response to anti-inflammatory treatment. Native T1 and T2 mapping may support an effective, noninvasive, radiation- and gadolinium contrast-free screening method for lupus myocarditis.